2022
DOI: 10.3390/jpm12111781
|View full text |Cite
|
Sign up to set email alerts
|

The Australian Reproductive Genetic Carrier Screening Project (Mackenzie’s Mission): Design and Implementation

Abstract: Reproductive genetic carrier screening (RGCS) provides people with information about their chance of having children with autosomal recessive or X-linked genetic conditions, enabling informed reproductive decision-making. RGCS is recommended to be offered to all couples during preconception or in early pregnancy. However, cost and a lack of awareness may prevent access. To address this, the Australian Government funded Mackenzie’s Mission—the Australian Reproductive Genetic Carrier Screening Project. Mackenzie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Non-pregnant increased Perspectives chance couples were also offered access to one subsidised IVF cycle for PGT. 23 Preliminary results from this study found that about 1 in 50 Australian reproductive couples will be identified as increased chance when expanded carrier screening is implemented. 24 We expect that the community, health economic and clinical benefits of expanded carrier screening will inevitably lead to widespread uptake in the near future.…”
Section: This Is Just the Beginning: Mackenzie's Mission And Expanded...mentioning
confidence: 89%
See 1 more Smart Citation
“…Non-pregnant increased Perspectives chance couples were also offered access to one subsidised IVF cycle for PGT. 23 Preliminary results from this study found that about 1 in 50 Australian reproductive couples will be identified as increased chance when expanded carrier screening is implemented. 24 We expect that the community, health economic and clinical benefits of expanded carrier screening will inevitably lead to widespread uptake in the near future.…”
Section: This Is Just the Beginning: Mackenzie's Mission And Expanded...mentioning
confidence: 89%
“…All increased chance couples were urgently referred to local genetics services for result counselling, support, follow‐up, and access to prenatal testing where requested. Non‐pregnant increased chance couples were also offered access to one subsidised IVF cycle for PGT 23 …”
Section: This Is Just the Beginning: Mackenzie's Mission And Expanded...mentioning
confidence: 99%
“…The tragic of a baby to SMA in Australia has fueled a large-scale reproductive carrier screening program for 750 genetic conditions ("Mackenzie's Mission") in Australia 19 . The estimated SMA incidence in both Arab countries studied here is signi cantly higher than that in other populations worldwide 7 , a nding which is consistent with the expectedly higher incidence of recessive disorders in Arab populations, suggesting that premarital genetic screening is likely to be an effective preventive measure in those populations.…”
Section: Sma Epidemiology Other Arab Populationsmentioning
confidence: 99%
“…A difficulty lies in addressing potential conflicts between commercial and patient interests. One article in the Special Issue contributes towards filling this gap identified by Edwards et al [ 9 ]. This paper details the protocol of the Australian reproductive genetic carrier screening project Mackenzie’s Mission to generate implementation evidence to inform a national program [ 9 ].…”
Section: Expanding Access To Genetic Counseling and Genetic Testingmentioning
confidence: 99%